Catalytic pyrolysis of film waste over Co/Ni pillared montmorillonites towards H₂ production - Li, Kaixin (2022)
The transformation of plastic waste into valuable fuel products via catalytic pyrolysis is a promising and eco-friendly strategy. Herein, a series of Co/Ni pillared montmorillonites were developed as low-cost and effective catalysts for the pyrolysis of post-consumer film waste, which is one of the representative plastic wastes in nature. The best-performing catalyst produced 80.2% of liquid product, with a high selectivity of 43.5% of hydrocarbons at C10-C13 range, and 42.0 vol% of H2 which is nearly increased by 40-fold as compared to that in non-catalytic run. The improved results were ascribed to the pillared structure, the oxidation state of Co/Ni, and the distribution of acid sites. Particularly, the Lewis acidity (which governs the cyclization and alkanisation) coupled with high surface area and uniform dispersion of transition metallic sites, were found to promote the selectivity of condensable product. The pyrolytic mechanism towards H2 production was explored by theoretical calculations. The lattice oxygen bonded to both Ni and Co in an octahedral environment was found to promote the adsorption of the fragment of polymer in dehydrogenation. Additionally, the solid residues are potentially applied for the production of valuable carbonaceous materials since they displayed high heating value. This work is expected to provide a direction for the development of pyrolysis technology for fuel production with sustainability and economic viability.